TYPHOID ENTERIC PERFORATION: PROGNOSTIC FACTORS AN EXPERIENCE WITH 76 PATIENTS - Khan, Afzal (Journal of Ayub Medical College Abbottabad, 2000)
Background: In spite of the world wide improvement in public awareness of hygiene and good sanitation there are still some parts of the world where the number of typhoid enteric perforation is rising day by day. Typhoid enteric perforation if on one hand is a cause of increased morbidity and mortality for the patients, on the other hand it is becoming a common surgical problem for the surgeon. Methods: A retrospective study of 76 patients of typhoid enteric perforation was carried out with the aim to evaluate the factors contributing to the increasing incidence & delayed diagnosis of the disease. More specifically the various surgical procedures used for the treatment of typhoid enteric perforation & its results were evaluated. All the 76 patients w-ere admitted in the Surgical "C" Unit of Khyber Teaching Hospital from January 1991 to Dec 1994. Results: The highest incidence was found in the second decade of life (36.84%). Male to female ratio was 2.1. The common presenting symptoms were fever (100%) followed by pain abdomen (76.31%). The Widal test was positive only in 71 patients while gas under the diaphragm was found in 45 cases. At Laparotomy 74 patients (97.36%) were found to have ileal perforation as compared to jejunal perforation in 2 cases. Faecal peritonitis was observed in 54 (59.21%). In 59 patients primary closure of the perforation was performed. While in 11 patient’s exteriorization of perforation as temporary ileostomy was performed. 12 patients out of 59 with primary closure of the perforation re-perforated and added to considerable postoperative morbidity and mortality. On the other hand, 11 patients with the primary exteriorization of perforation as temporary ileostomy did very well The overall mortality rate was (22.35%). Conclusion: Early diagnosis and primary exteriorization of the perforation as temporary ileostomy can decrease morbidity and mortality considerably.